UV light crosslinking regresses mature corneal blood and lymphatic vessels and promotes subsequent high‐risk corneal transplant survival. Issue 12 (26th May 2018) - Hou, Yanhong; Le, Viet Nhat Hung; Tóth, Gábor; Siebelmann, Sebastian; Horstmann, Jens; Gabriel, Tim; Bock, Felix; Cursiefen, Claus
Abstract : Immunologic graft rejection is the main complication after corneal transplant into pathologically prevascularized so‐called high‐risk eyes. The aim of this study was to evaluate whether ultraviolet (UV) light crosslinking can regress pathologic corneal blood and lymphatic vessels and thereby improve subsequent graft survival. Using the murine model of suture‐induced corneal neovascularization, we found that corneal crosslinking with UVA light and riboflavin regressed both preexisting blood and lymphatic vessels significantly via induction of apoptosis in vascular endothelial cells. In addition, macrophages and CD45 + cell counts were significantly reduced. Consistently, corneal crosslinking reduced keratocyte density and corneal thickness without affecting corneal nonvascular endothelial cells, iris, and lens depending on the crosslinking duration. Furthermore, using the murine model of corneal transplant, long‐term graft survival was significantly promoted ( P  < .05) and CD4 + CD25 + FoxP3 + T regulatory cells were upregulated ( P  < .01) in high‐risk eyes preoperatively treated with crosslinking. Our results suggest UV light crosslinking as a novel method to regress both pathologic corneal blood and lymphatic vessels and to reduce CD45 + inflammatory cells. Furthermore, this study demonstrates for the first time that preoperative corneal crosslinking in prevascularized high‐risk eyes can significantly improve subsequent graft survival and may become a promising novel therapy in the clinic. Abstract : Corneal crosslinking with ultraviolet‐A light and riboflavin can regress mature pathological corneal blood and lymphatic vessels, thereby promoting graft survival of a prevascularized high‐risk corneal transplantation.